Exercised-Induced Coronary Spasm in Near Normal Coronary Arteries - Damian Franzen; Thomas Benzing (International Journal of Vascular Medicine)
In contrast to effort-induced symptoms in obstructive coronary disease, spasm in normal coronary arteries is characterized by angina at rest. We describe a 44-year-old patient with minor coronary plaques and pure exercised-induced coronary spasm. The case questions the differential pathogenic considerations of variant of the variant as opposed to Prinzmetal's variant angina.